Geologia estrutural do segmento oeste da Serra do Curral, Quadrilátero Ferrífero, e o controle tectônico das acumulações de alto teor em Fe - Julio Carlos Destro Sanglard (2013)
The structure of western Serra do Curral, Quadrilátero Ferrífero represents the partial exposure of a syncline that verges to NNW – Piedade Syncline. This regional structure has parasitic folds denominated as B1A, which are refolded by folds B1B that also have vergence to NNW. Both of them have NNE-WSW direction, are non-cylindrical folds, and configure an interference pattern that is similar to Type 3 from Ramsay. This refolding occur during progressive deformation. The occurrence of hypogenic high-grade martitic-hematitic-specularitic accumulation is controlled by the combination of these folds and high angle thrust fault, both with the same direction. These accumulations have low REE+Y contents, between 6 and 97 ppm, and occur as itabirite’s hosted bodies of Cauê Formation or as massive veins in Piracicaba Group’s rocks. Inside the veins, there are detritic archean zircon grains incorporated from the host rocks and they show heavy REE enrichment compared with light REE when normalized by PAAS. The itabirite hosted accumulations show positive Eu anomaly and two different normalization patterns: one with mean REE+Y concentration of 14 ppm and heavy REE enrichment compared with light REE, such as the itabirite pattern, the other one shows mean REE+Y concentration of 85 ppm and high light REE content. This last pattern is characterized by its content on monazite grains that occur on textural balance with the iron oxides. Over the ENE-WSW structures there is a development of folds with NNW-SSE direction and WSW vergence (B2 folds). These folds are restricted to the B1A and B1B limbs and they configure an interference pattern named ‘abbuting fold’. The age obtained by U/Pb SHRIMP on monazite grains is 2034 ± 11 Ma. This age corresponds to the formation timing of the high-grade bodies and suggests that the mineralization process, at least at the western Serra do Curral, is contemporary to the metamorphic peak of Quadrilátero Ferrífero region during the Transamazonian orogeny.